Study on the adaptability and optimization of boom replacement methods for suspension bridges - Mu, Yingna; Hu, Qibing; Chen, Changping; Tan, Yanbin; Zheng, Yanna; Liang, Guoxuan (Frontiers in Materials, 2023)
To ensure the safe operation of bridges, the study of methods and techniques for boom replacement has become a crucial aspect of the scientific maintenance of suspension bridges. This study focuses on analyzing the bridge responses and evaluating the applicability of three different boom replacement methods: single-point, three-point and five-point, using finite element calculations. A sea-crossing suspension bridge is taken as a case study to simulate the process of boom replacement using temporary booms. Consequently, the optimal replacement method for booms of varying lengths is determined. Meanwhile, this research proposes a quantitative basis for classifying boom lengths based on calculation data and analysis results to determine the suitable boom lengths for different replacement methods. Besides, a comparison of the relationship between the force transmission efficiency of temporary booms and boom length reveals that longer booms exhibit lower force transmission efficiency, with the efficiency decreasing at a faster rate as boom length increases. Overall, these findings provide a theoretical basis for the study of boom replacement in suspension bridges.